Arizona Tucson Mission: a report and history : July 1, 1996 to June 30, 1999 - Andrus, Alyn Brown (1999)
pt. 1. Introduction -- pt. 2. The Arizona Tucson Mission -- Boundaries and geography -- Organization -- Branches -- From inception of the Mission to the McKinlays -- pt. 3. The McKinlay approach -- pt. 4. Mission resources and procedures, non-missionary -- Apartment coordinators and apartments -- Financial secretary and finances -- Fleet coordinator: commissary, pagers, vehicles -- Mission secretary: office manager, missionary medical, reporting baptisms -- Referral secretary and referrals -- pt. 5. Mission resources and procedures, missionary-related -- Transfer planning, transfers, missionary departures and arrivals -- Assistants to the President: ZLCM and training tours -- Statistics and statistical reporting -- Unified Missionary Plan -- Mission tours, visits by General Authorities, and conferences -- The Mission Voice -- Investigator firesides -- pt. 6. Autobiographies -- Mission presidency -- Staff members -- pt. 7. Missionary spiritual experiences -- pt. 8. Missionary names and addresses -- pt. 9. Appendix -- Mission map -- Welcome to the Arizona Tucson Mission booklet -- Arizona Tucson Mission duties -- Responsibilties of a Zone Leader: a month in the life of a Zone Leader / Travis Olsen -- A day in the life of a missionary / Kimberlee Frederick -- District Meeting agenda -- Zone conference and ZLCM agendas -- Zone conference themes -- Alamogordo District Conference agenda -- Unified Missionary Plan -- List of special meetings and visiting dignitaries, July 1, 1996 through June 30, 1999 -- Baptism information [statistics] -- The Mission Voice -- Investigator fireside lectures.